Kesetaraan dalam Pendidikan Sebagai Praksis Responsif Gender Era Society 5.0 di Pesantren - Imaniyatul Fithriyah; Shahibul Muttaqien Al-Manduriy; Ach Sayyi; Saihul Atho’ A’laul Huda (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2022)
The presence of the era of society 5.0 has a positive impact on every individual, one of which is the creation of the widest possible employment opportunities to improve the welfare of society, including women. However, in reality, until now, there are still many women who have not been absorbed in every moment of recruitment in various institutions, both public and private institutions. This paper seeks to reveal the praxis and model of equality in education in Islamic boarding schools in gender responsiveness. This research method has a multi-site study design, namely a qualitative research design involving more than one site that has the same principles as a single case study. Data was collected through observation, interviews, and document studies. Then analyzed through data reduction, display verification data. The results showed that the implementation of education at the Al-Kautsar Lawangan Daya Pamekasan Islamic Boarding School both provided the widest opportunity for all students, including female students, to complete their education to college wherever they wanted, and not infrequently alumnus female students Islamic boarding schools who continue abroad. Gender responsiveness is implied by giving equal portions between male and female students to explore their respective live skills in the form of policies and structured learning.